4CPS-007 Pharmaceutical care as a means of prevention against drug iatrogenesis: case of oral anticoagulants. (24th March 2020) - Andre, D; Chatain, C; Chaumais, MC; Rieutord, A; Roy, S
Abstract : Background and importance: Oral anticoagulants (OAC) have a significant risk of adverse events, particularly in the transition of care were OAC are initiated, modified or transitionally interrupted. Pharmaceutical care through medication reconciliation and patient counselling could improve the benefit to risk ratio of these drugs. Aim and objectives: To use OAC therapy as prioritisation criteria for performing pharmaceutical care: medication reconciliation and pharmaceutical counselling. Material and methods: A prospective and interventional single centre study was conducted from March to September 2018 in the medicine and surgical units. Patients with an OAC prescribed from the outpatient sector were included. These patients received medication reconciliation at admission and discharge as well as patient specific pharmaceutical counselling about OAC to provide education. Their knowledge was assessed with a multiple choice questionnaire. Frequency and type of reconciliation discrepancies were studied at admission and discharge. The gravity rating of this discrepancies was measured using the Cornish et al scale, with three levels of severity: low, moderate and high. At patient discharge, a summary of the knowledge acquired by the patient about OAC and medication reconciliation was provided to them. Results: A total of 162 patients were included in the study. Medication reconciliation at admission allowed the detection of 133 unintentional discrepancies (0.8/patient) of which 16 represented a high risk to the patient, including 9 errors about OAC prescribing. Concerning medication reconciliation at discharge, 51 unintentional discrepancies (0.3/patient) were detected: 12 represented a high risk to the patient, including 8 errors about OAC prescribing. The acceptance rate of the discrepancies was 86% in total and reflected the degree of severity of the pharmaceutical interventions. This result reached 96% if we took into account discrepancies with a real clinical impact. Concerning the pharmaceutical multiple choice questionnaire, the success rate was 66%. Conclusion and relevance: This study has highlighted that OAC represents a relevant criterion of prioritisation to the long term implementation of pharmaceutical care. This secures the management of patients receiving OAC if pharmaceutical care is present along the whole route of care, from admission to discharge. The last step of our approach will be improvement in the transmission of data to community caregivers. References and/or acknowledgements: No conflict of interest.